Inovasi Kerajinan Serat Paku Hata (Lygodium circinatum) Khas Citumang, Jawa Barat - Fajar Ciptandi; Rachmah Firstriani; Sisca Dewi (JURNAL RUPA, 2021)
In Citumang Village of Pangandaran Regency in West Java, Hata ferns (Lygodium circinatum) plants thrive. Citumang people use the abundance of this plant to make handicraft products such as bags, hats, and wall hangings. However, the products made by Hata ferns craftsmen at Citumang do not yet have their characteristics, so often, their bags are said to be the same as crafts in Bali and Lombok. That is due to the lack of development in design, colors, and techniques of the Citumang Hata ferns handicraft products. Experiments on natural coloring, structural design, and motif composition designs were carried out to enhance the characteristics of the handicraft,. Thus Hata ferns craftsmen at Citumang can innovate by applying the experiment to bag products. The experiment finally succeeded in showing the characteristics of Hata ferns handicraft products with makes it more aesthetic. This experiment also helped develop creativity and add insight into the craftsmen at Citumang.